CURRENT TREND IN NAMING BABIES IN JAVANESE COMMUNITY - Carla Sih Prabandari (International Journal of Humanity Studies (IJHS), 2017)
The process of naming newborn babies is inseparable from the culture where they belong. Among Javanese people, there is a change of trends in naming babies. As western, noble, and religion associated names, such as Amelia, Gupita, Arsyad, gain popularity, modest and old-fashioned names, such as Tugino and Pariyem disappear. This paper discusses the trend in the naming of babies in Javanese community at the present time. Three theories are employed in the analysis. I will apply Saussurean Semiology and Bathesian Semiology and try to relate them to Stuart Hall's Theory of Identity. As a name is just an element of cultural identities, changing trends in naming in Javanese culture does not entirely change their identity as Javanese people.